CFTR Correctors and Antioxidants Partially Normalize Lipid Imbalance but not Abnormal Basal Inflammatory Cytokine Profile in CF Bronchial Epithelial Cells - Veltman, Mieke; De Sanctis, Juan B.; Stolarczyk, Marta; Klymiuk, Nikolai; Bähr, Andrea; Brouwer, Rutger W.; Oole, Edwin; Shah, Juhi; Ozdian, Tomas; Liao, Jie; Martini, Carolina; Radzioch, Danuta; et al. (Frontiers in Physiology, 2021)
A deficiency in cystic fibrosis transmembrane conductance regulator (CFTR) function in cystic fibrosis (CF) leads to chronic lung disease. However, the molecular mechanisms are not well understood and therapies that can help all patients remain elusive. CF is associated with abnormalities in fatty acids, ceramides and cholesterol. Therefore, we examined the impact of CFTR deficiency on lipid metabolism and pro-inflammatory signaling in airway epithelium using mass spectrometric, protein array and RNAseq analyses. We observed a striking imbalance in fatty acid and ceramide metabolism, associated with chronic oxidative stress under basal conditions in CF mouse lung and well differentiated bronchial epithelial cell cultures of CFTR knock out pig and CF patients. Cell autonomous features of all three CF models included high ratios of ω-6- to ω-3-polyunsaturated fatty acids and of long- to very long- chain ceramide species (LCC/VLCC), reduced levels of total ceramides and ceramide precursors. In addition to the retinoic acid analogue fenretinide, the anti-oxidants glutathione (GSH) and deferoxamine partially corrected the lipid profile indicating that oxidative stress may promote the lipid abnormalities. CFTR-targeted modulators reduced the lipid imbalance and oxidative stress, confirming the CFTR dependence of lipid ratios. However, despite functional correction of mutant cells up to 60% of non-CF in Ussing chamber experiments, a 72-hour triple compound treatment (Trikafta surrogate) did not completely normalize lipid imbalance or oxidative stress. RNA sequencing and protein array analysis revealed differential expression and shedding of cytokines and growth factors from CF epithelial cells compared to non-CF cells, consistent with sterile inflammation and tissue remodeling under basal conditions, including enhanced secretion of the neutrophil activator CXCL5, and the T-cell activator CCL17. However, treatment with antioxidants or CFTR modulators that mimic the approved combination therapies, Orkambi and Trikafta, did not effectively suppress the inflammatory phenotype. We propose that CFTR deficiency causes oxidative stress in CF airway epithelium, affecting multiple bioactive lipid metabolic pathways, which likely play a role in CF lung disease progression. A combination of anti-oxidant, anti-inflammatory and CFTR targeted therapeutics may be required for full correction of the CF phenotype.